(untitled) (Annals of Medical Research, 2021)
Aim: The extension of the maxillary sinus is an important issue for fixed orthodontic treatments and maxillofacial surgery. The aim of this study is to investigate the dimensions and volume of the maxillary sinus in different skeletal classes and, also the effect on the anteroposterior growth pattern of the maxilla.Materials and Methods: The cone-beam computed tomography (CBCT) images of 48 patients were obtained from the archive of the Department of Oral and Maxillofacial Radiology. The CBCT images were taken prior to orthognathic surgery for the surgical planning of all patients. According to the sagittal skeletal position of the maxilla, the patients were divided into three groups: normal maxilla group, retrognathic maxilla group and, prognathic maxilla group. Dimensional and volumetric measurements of the maxillary sinus were performed by the same oral and maxillofacial radiologist.Results: Although no statistical difference was observed between different skeletal groups regarding the maxillary sinus dimensions and volume, the results did show that there was an inverse and statistically significant correlation between the left maxillary sinus width and age (p0.05). There was a statistically significant difference between males and females for the width, height, and depth of right maxillary sinus, the right maxillary sinus volume, the height and depth of left maxillary sinus.Conclusion: In conclusion, for orthodontists and maxillofacial surgeons, the dimensional and volumetric measurements performed by CBCT act as a pathfinder role in the insertion of miniscrews, orthodontic tooth movement through the maxillary sinus, and the orthognathic surgeries such as Le Fort osteotomies.